The Role of Cultural Activities in Preserving the Palestinian Idntity in Occupied East Jerusalem - SHURRAB, HATEM M. M. (İstanbul Kültür Üniversitesi, 2023)
The Israel-Palestine conflict in the city of Jerusalem is not only about who dominates control over the land and religious sites, but it includes a cultural struggle used as a soft power. Palestinians have faced massive challenges in preserving their national identity in the city, so this research attempts to examine Palestinian cultural efforts against the Israeli narrative. The study adopted reliable methods including qualitative, historical and exploratory research and interviews with Palestinians working in the cultural field, the study focused on how Palestinians handle the Israeli policies and restrictions - against cultural activities - to emphasize the Palestinian identity of Jerusalem. The study found out the major obstacles facing Palestinians in preserving their identity in the city which were objective because of the bitter reality of the occupation, and subjective because of the shortcomings in managing the cultural field in Jerusalem. The findings of the study were that the Palestinians partially succeeded in reviving the Palestinian cultural narrative as means of preserving identity, but not in the desired manner, due to the difference in the balance of power that tends in favor of the occupation. The study concluded with many recommendations, the most important was to consolidate efforts by all stakeholders including scholars, religious figures, intellectuals, Palestinian organizations and supporters to empower and improve the Palestinian cultural presence in the city. Along with providing the necessary financial support to establish and support cultural activities and Palestinian steadfastness in Jerusalem in general.
İşgal Altındaki Doğu Kudüs'te Filistin Kimliğinin Korunmasında Kültürel Faaliyetlerin Rolü
▪ Yüksek lisans tezi.
Keywords: Palestine-israel Conflict; Soft Power; East Jerusalem; National Identity; Art and Culture; Palestine; Heritage; Israel; History of Jerusalem; Capital of Palestine